LDCs move into human capital intensive industries: The case of Brazil's nonelectrical machinery sector - Jan Peter Wogart (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1989)
In the 1987 study On the Determinants of Brazilian Exports, two hypotheses figured prominently. First, it was stated that Brazil's comparative advantage was in unskilled labor intensive products and secondly that policy interventions rather than internal factors were responsible in fostering Brazil's capital intensive exports . By following the advice to investigate these issues in more detailed studies for individual sectors of industry, this essay is challenging those two postulates and will provide evidence to come to different conclusions.
Keywords: 330; Maschinenbau; Maschinenmarkt; Werkzeugmaschine; Internationaler Wettbewerb; Brasilien